Program Bimbingan Belajar Berdasarkan Profil Academic Self-Efficacy Santri (Studi Deskriptif di SMP IT Baitul Anshor Boarding School dan Pondok Pesantren Baitul Izzah Cimahi Tahun Ajaran 2018/2019) - Karimah, Aulia; Simanjuntak, Kristina; Atmadja, Fitriani Putri (Jurnal Pendidikan Indonesia, 2022)
Academic Self-Efficacy refers to one’s confidence and beliefs about their own abilities to accomplish task and academic demands. Santri or students in junior high school considered as adolescences and still need helps to develop their abilities in academic because their lack of confidences about their level on ability in academic domain. The purpose of this research is to find out about academic self-efficacy santri. The research approached is quantitative approach with descriptive method. Population in this study are santri from Junior High School Baitul Anshor Boarding School dan Baitul Izzah Boarding School academic year 2018/2019. The sample for this research consisted of 67 santri from Baitul Anshor Boarding School and 78 santri from Baitul Izzah Boarding School and using probability sampling with smple random sampling with 0.05 error level. The results of this research show that general overview is in medium category. The result form this research is guidance program that has been tested by the experts and guidance and counseling praticer or school counselor.